Infrastructure in Central Asia and Caucasia - Ghulam Samad; Qaisar Abbas (Asian Development Bank Institute (ADBI), 2020)
Without realizing the importance of soft infrastructure, hard infrastructure cannot ensure a significant impact on sustained economic development. Unfortunately, Central Asia and Caucasia regions have continued to rely on a physical development model that has resulted in generating revenue but has failed to embed a sustained growth pattern in these countries. This paper highlights where Central Asia and Caucasia regions stand in terms of physical and soft infrastructure. A gradual improvement in physical infrastructure is observed, however, the infrastructure development pattern is uneven. Tajikistan and the Kyrgyz Republic are catching up with the rest of the region. The utilization of infrastructure depends on regional infrastructure connectivity which shows gradual improvement but still faces challenges, for example, mandatory transloading, corruption and inappropriate practices, containerization availability, and multi-transport mode delays. To overcome infrastructure development and connectivity challenges, massive infrastructure investment is required but is currently quite low. To tap infrastructure financing, appropriate financing strategies like developing public-private partnerships, attracting foreign direct investment, and exploring the possibility of the bond market are required. To improve the infrastructure development landscape, and resolve infrastructure connectivity and financing issues, the region requires an appropriate institutional and regulatory environment.
Keywords: O18; R42; H11; 330; infrastructure; transportation infrastructure; roles of government